2023
DOI: 10.1039/d2dt04108a
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) complex enhanced chemodynamic therapy through GSH depletion and autophagy flow blockade

Abstract: Three copper(II) complexes C1–C3 were synthesized and fully characterized as chemodynamic therapy (CDT) anticancer agents. C1–C3 showed greater cytotoxicity than their ligands toward SK-OV-3 and T24 cells. Particularly, C2 showed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… 31 , 37 Copper‐induced ROS also increase lipid peroxidation, deplete glutathione (GSH) and enhance cellular susceptibility to oxidative damage. 38 Moreover, copper accumulation in the cell nucleus damages DNA in various biological systems and inactivates sulphur‐containing enzymes by binding to their sulphur groups. 39 Additionally, copper ions inhibit the chymotrypsin‐like activity of the 20S proteasome and 19S proteasomal deubiquitinases, further inducing apoptosis.…”
Section: The Physiological Homeostasis and Metabolism Of Coppermentioning
confidence: 99%
See 1 more Smart Citation
“… 31 , 37 Copper‐induced ROS also increase lipid peroxidation, deplete glutathione (GSH) and enhance cellular susceptibility to oxidative damage. 38 Moreover, copper accumulation in the cell nucleus damages DNA in various biological systems and inactivates sulphur‐containing enzymes by binding to their sulphur groups. 39 Additionally, copper ions inhibit the chymotrypsin‐like activity of the 20S proteasome and 19S proteasomal deubiquitinases, further inducing apoptosis.…”
Section: The Physiological Homeostasis and Metabolism Of Coppermentioning
confidence: 99%
“…This process leads to the release of cytochrome c and mitochondrial apoptosis‐inducing factor 1 into the cytoplasm, initiating caspase activation and DNA fragmentation 31,37 . Copper‐induced ROS also increase lipid peroxidation, deplete glutathione (GSH) and enhance cellular susceptibility to oxidative damage 38 . Moreover, copper accumulation in the cell nucleus damages DNA in various biological systems and inactivates sulphur‐containing enzymes by binding to their sulphur groups 39 .…”
Section: The Physiological Homeostasis and Metabolism Of Coppermentioning
confidence: 99%
“…20 Cu( ii ) undergoes a redox reaction with GSH to generate oxidized glutathione (GSSG) and Cu( i ), which catalyzes the conversion of H 2 O 2 to ROS. 21–24 Moreover, copper complexes are less toxic than traditional platinum drugs. 25,26 Therefore, it is a promising strategy to use copper complexes to amplify ˙OH induced oxidative stress and reduce GSH to enhance the CDT effect.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that excessive oxidative stress can increase the membrane permeability of lysosomes and lead to lysosome dysfunction. 20 It also impairs the ability of the autophagolysosome to recycle nutrients. In addition, nanomedicines are often localized in lysosomes, and oxidative stress generated by nanomaterials may more effectively block autophagy flux at a later stage.…”
mentioning
confidence: 99%
“…Various enzymes in the lysosome, such as protease, glycosidase, and phosphatase, complete the recovery of nutrients. Some studies have shown that excessive oxidative stress can increase the membrane permeability of lysosomes and lead to lysosome dysfunction . It also impairs the ability of the autophagolysosome to recycle nutrients.…”
mentioning
confidence: 99%